Effect Of Social Media Enabled Learning In Enhancing Achievement In Physics At Higher Secondary Level - K, Mr. Denny John.; Sreedevi, Dr. P. S. (Voices of Teachers and Teacher Educators, 2021)
The technology is advancing day-by-day. The advent of new millennia has brought tremendous changes in all the fields. The spread of COVID-19 has drastically affected human lives as well as the global economy. The after-effects of this deadly disease have reached the education sector too. Technical advancement urges for experimenting new technology in the field of learning and teaching pedagogy, to help overcome the present crisis. Social Media Enabled Learning (SMEL) provides a massive opportunity in the education sector. This study deals with the application of WhatsApp–a user friendly social media platform, as an educational tool, to provide learning experiences and assess the achievement of students in physics at the higher secondary level. Keywords: Social media, Social media enabled learning.